2015
DOI: 10.1177/0004867415587341
|View full text |Cite
|
Sign up to set email alerts
|

Age at first tobacco use and risk of subsequent psychosis-related outcomes: A birth cohort study

Abstract: There is an association between age at first tobacco use and subsequent psychosis-related outcomes in young adults. While the findings cannot be used to deduce causality, it adds weight to the hypothesis that early tobacco use may contribute to the risk of developing psychosis-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…Early initiation of daily smoking was also a slightly greater risk factor for psychosis compared with late initiation of daily smoking even after adjusting for many potential confounders. This result is consistent with a previous study (21), which showed that earlier initiation of ever-smoking was associated with psychosis outcomes. It can be speculated that earlier onset of smoking could result in a greater cumulative dose of nicotine or other harmful byproducts from tobacco over time.…”
Section: Discussionsupporting
confidence: 93%
“…Early initiation of daily smoking was also a slightly greater risk factor for psychosis compared with late initiation of daily smoking even after adjusting for many potential confounders. This result is consistent with a previous study (21), which showed that earlier initiation of ever-smoking was associated with psychosis outcomes. It can be speculated that earlier onset of smoking could result in a greater cumulative dose of nicotine or other harmful byproducts from tobacco over time.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, in keeping with previous studies of PEs, 3,9,18,19 we excluded respondents who (a) reported (1) schizophrenia/psychosis or (2) manic-depression/mania in response to the question “ What did the doctor say was causing (this/these) experiences?” ; and (b) those who ever took an antipsychotic medication for these symptoms. This resulted in the exclusion of 146 respondents (0.4% of all respondents), leaving 33,370 respondents for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Gurillo, Jauhar, Murray, and MacCabe (2015) identified that cigarette smoking was prevalent in young people with first episode psychosis, and that smokers developed psychosis at an earlier age than nonsmokers. Smoking can cause many negative life-threatening health outcomes and is widely recognized as a risk factor of comorbid physical health problems (Gurillo et al, 2015;McGrath et al, 2016). It also potentiates adverse pharmacotherapy effects because the nicotine consumed from smoking cigarettes interferes with the metabolism of antipsychotic medication (McGrath et al, 2016).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%